Dynamic output characteristics of a photovoltaic-wind-concentrating solar power hybrid system integrating an electric heating device. (1st August 2019) - Han, Xue; Pan, Xinyu; Yang, Hao; Xu, Chao; Ju, Xing; Du, Xiaoze
Highlights: A photovoltaic-wind-concentrating solar power hybrid system integrating an electric heater is proposed. The hybrid system is effective to reduce the power rejection and match the load demand. The dynamic output characteristics and economic performance of the hybrid system are analyzed. An optimal configuration is proposed considering various influencing factors. Abstract: A large-scale renewable photovoltaic-wind-concentrating solar power hybrid system integrating an electric heating device is proposed to provide a sustainable power for a domestic region. The thermal energy storage and the electric heating device can be utilized to recover the power rejection from the photovoltaic and wind systems, and match the flexible load demand. In this research, a dynamic physical model is established to analyze the dynamic output characteristics based on the renewable resources and load demand in Zhangbei area, China. The results prove that the hybrid system can well match the load demand most of the time, and the power rejection can be recovered by about 20–35%. The Levelized Cost of Energy achieves its lowest level at the fixed capacities of photovoltaic and wind systems. Further, the recovery ratio is inversely proportional to the solar multiple and the capacities of the photovoltaic and wind systems, while it improves with the increase of the thermal energy storage capacity. The Levelized Cost of Energy of 0.2775 /kWh and the recovery ratio of 30.87% are achieved when the hybrid system is composed of 900 MWe photovoltaic, 3600 MWe wind, and 1360 MWe concentrating solar power system at the solar multiple of 1.2 and the thermal energy storage capacity of 190 GWht, given the loss of power supply probability of 5%.